Keterampilan Komunikasi Penyuluh dan Partisipasi Petani dalam Kegiatan Penyuluhan Padi Sawah di Desa Wonua Monapa Kecamatan Pondidaha Kabupaten Konawe - Sri Hardianti; Iskandar Zainuddin Rela; Salahuddin Salahuddin (Fakultas Pertanian Universitas Halu Oleo, 2021)
The agricultural sector is one of the important sectors in national economic development. Participation of farmers both individually and in groups with full awareness and responsibility in the field of agricultural business is indispensable to create changes that can improve the welfare of farmers. To increase farmers' participation, the role of agricultural extensionists is very important. This research aimed to knowed the level of communication skills of extension workers, the level of participation of farmers and to know the relationship of communication skills to the participation of farmers in rice paddy extension activities in wonua monapa village pondidaha district konawe. Sampling is determined randomly or simple random sampling with the number of samples as many as 43 respondents rice paddy farmers. The techniques of data analyzed used to determine extension communication skills and farmer participation are measured using a likert scale and then analyzed using a class interval formula and to find out the relationship of extension communication skills to farmer participation using spearman rank correlation formula. The results showed that the communication skills of extension workers with a moderate category with a percentage of 76.74%, the participation of farmers with a moderate category with a percentage of 58.14%. Rank Spearman's correlation test results showed that extension communication skills with farmers' participation in rice paddy extension activities showed significance or Sig value. (2-tailed) of 0.030<0.05, so Ha was accepted. That is, the improved communication skills of extension workers, the participation of farmers will also increase.